Violation of Subjective Rights as the Basis for an Unlawful Act - Kimmy Baby Kirana; Imelda Martinelli (Publikasi Indonesia, 2026)
In modern civil society, conflicts of interest often arise from acts that cause harm to others, yet not all such acts are clearly regulated by written law, creating legal uncertainty for victims seeking justice. This research aims to analyze the concept of unlawful act (tort) in Indonesian Civil Law based on violations of subjective rights and to examine judicial considerations in determining the fulfilments of the elements of tort in judicial practice. This research employed a normative juridical method with statutory and case approaches, analyzed using descriptive qualitative method. The results indicate that the concept of unlawful act (tort) has evolved from a narrow interpretation limited to violations of written law into a broader interpretation encompassing violations of subjective rights, moral norms, and principles of propriety. The elements of tort consist of an act, unlawfulness, fault, damage and a causal relationship, all of which must be cumulatively proven. In judicial practice, the application of these elements still reflects decision disparities due to differing judicial interpretations. The analysis of decision Number 2579 K/Pdt/2025 demonstrates that violations of subjective rights, particularly proprietary rights over land certificates, may serve as the primary basis for establishing an unlawful act, even in the absence of explicit statutory violations. The novelty of this journal lies in emphasizing the central positions of subjective rights violations as a foundational basis of constructing unlawful acts in Indonesian civil law practices.